103k views
0 votes
Solve the equation: 5 + 2(3 + 2x) = x + 3(x + 1)

User Aethex
by
6.2k points

1 Answer

4 votes

Answer:

No solutions

Explanation:

In this question, you would be solving for x.

Solve:

5 + 2(3 + 2x) = x + 3(x + 1)

Use the distributive property.

5 + 6 + 4x = x + 3x + 3

Combine like terms.

11 + 4x = 4x + 3

Subtract 4x from both sides.

11 = 3

Since we don't have an "x value", there are no solutions.

"No solutions" would be your answer.

User Elman Huseynov
by
6.6k points